Indonesian Mining Regulations Shift as a Potential Sector in Developing the Economy - Amanda Adelina Harun; Fenty U Puluhulawa; Nurul Fajri ElFikri; Mohamad Rivaldi Moha (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Law/regulation on mining play a significant role, because mining sector is a potential sector for developing the economy of Indonesian. Law on Mining underwent several amendments, namely the era of Law Number 11 of 1967, Law Number 4 of 2009 and Law Number 3 of 2020. This article will analyze shiftss in mining sector regulations from each of these eras. This article uses normative juridical methods, with statutory, contextual, historical, and comparative approaches, and is analyzed qualitatively. The results of the study show that between Law No. 11 of 1967 to Law No. 4 of 2009 and Law no. 3 of 2020 underwent a change, namely from a centralized arrangement, where the mining sector holding power became a matter for the central government to decentralization, handed over to local governments. Another change is in the field of relations between the government and capital or investors, the contract of work model becomes licensing. The impact on the contract of work model is that the state is positioned as a 'party' to the contract, while in terms of licensing the government has a position that tends to be stronger. This Amendment Contract is adapted to Indonesian conditions and the protection of Article 33 of the Indonesian constitution.